Water Quality Status of Three Different Rivers for Fadama-oriented Irrigated Agriculture in Ogbomoso, Southwest Nigeria - , Toyin Peter Abegunrin; , Gabriel Oladele Awe; , Modupe Adebola Adejumobi (Archives of Current Research International, 2016)
Aims: The objective of this study was to evaluate water quality status of rivers OBA, ORA and SUNSUN for irrigated agriculture in Ogbomoso, Southwest Nigeria. Study Design: Data were analyzed using 2 x 3 factorial design, with two sampling sites and three sampling periods as treatments in three replications. Place and Duration of Study: The experiment was conducted in six Fadama sites along three rivers (Oba, Ora, and Sunsun) in Ogbomoso located on Latitude 8° 10’N and Longitude 4° 10’E, about 342 m above the mean sea level, southwest Nigeria between December 2014 and March 2015 during the 2014/2015 irrigation (dry) season. Methodology: Water samples were collected from two representative Fadama sites along each river and at three different periods during the 2014/2015 irrigation season for the determination of water quality indicators and overall water quality index (WQI). Results: There was significant temporal variation in the water quality indicators of the three rivers. Except for permeability index (PI), other integrated water quality characteristics of SAR, KI, SSP, ESP, MI and RSC varied significantly (p<0.05) with respect to sampling site and period, and the average values were within permissible limits for irrigation. Of the three rivers, only River SUNSUN had salinity and sodicity classification of C3-S1 and water quality index of class III during a particular period. Conclusion: The results from SUNSUN River showed that care must be taken in using the river for irrigation, especially at the peak of dry season, because of salinity problem. Further studies is also recommended for heavy and trace metals contamination as a result of the observed anthropogenic activities in the vicinity of the river bodies.